Cardiovascular Responses to an Isometric Handgrip Exercise in Females with Prehypertension - Bond, Vernon (N Am J Med Sci, 2016)
BACKGROUND: Hypertensive individuals are known to exhibit greater increases in blood pressure during an isometric handgrip exercise (IHE) than their normotensive counterparts. AIM: This study tests the hypothesis that, compared to normotensive individuals, prehypertensive individuals exhibit an exaggerated response to IHE. MATERIALS AND METHODS: In this study, the effects of IHE were compared in matched prehypertensive vs. normotensive healthy African-American females. Six healthy young adult African–American female university students were screened in a physician's office for blood pressure in the range of prehypertension, systolic blood pressure (SBP) 120–139 mmHg and diastolic blood pressure (DBP) 80–89 mmHg. Six young adult African–American women were also recruited to serve as a healthy normotensive control group with SBP ≤119 mmHg and DBP ≤79 mmHg. Cardiovascular fitness was determined by peak oxygen uptake (VO(2) peak) measured during a progressive exercise test. RESULTS: During the handgrip exercise, the prehypertensive group exhibited greater increases in SBP (from 139 ± 6 to 205 ± 11 mmHg, +48%) than the controls (from 132 ± 3 to 145 ± 3 mmHg, +10%); intergroup difference P < 0.001. The prehypertensive group also exhibited greater increases in DBP (from 77 ± 2 to 112 ± 5 mmHg, +46%) compared to the controls (from 72 ± 3 to 78 ± 4 mmHg, +8%); intergroup difference P < 0.001. The increase in systemic vascular resistance was also greater in the prehypertensive group (from 1713 ± 91 to 2807 ± 370 dyne.s.cm(-5), +64%) than in the controls (from 1668 ± 80 to 1812 ± 169 dyne.s.cm(-5), +9%); intergroup difference P < 0.05. CONCLUSION: These results suggest that blood pressure measurements performed during IHE may be a useful screening tool in evaluating prehypertensive individuals for antihypertensive treatments.